Relationship between acoustic impedance and porosity of Pratu Tao Formation in the Greater Pratu Tao area, Phitsanulok Basin, Thailand - Suhattaya Kaewla-iad (Chulalongkorn University, 2008)
Thesis (M.Sc.)--Chulalongkorn University, 2002